Optimal law enforcement when individuals are either moral or norm followers - Claude Fluet; Tim Friehe (Journal of Public Economic Theory, 2023)
Moral rules and social norms influence whether individuals break the law. We characterize optimal law enforcement when some individuals obey internalized moral rules and implement social norms for other individuals who prefer to comply with them. Moral individuals and norm followers are linked via the endogenous social norm and this induces the social planner to create an expected sanction for norm setters that is higher than without the link. The optimal expected sanction for moral individuals is higher than the one for norm followers if the moral rule is weak but the reverse ranking is true when it is strong.
Keywords: 330; crime; law enforcement; morality; social norm